THE PSYCHOBIOLOGY OF AGRESSIVE BEHAVIOURS - Gil Verona, José Antonio; Pastor, Juan Francisco; De Paz, Félix; Barbosa, Mercedes; Macías, José Ángel; Maniega, María Antonia; Rami-González, Lorena; Boget, Teresa; Picornell, Inés (Anales de Psicología / Annals of Psychology, 2002)
With this paper we have made a revision of what aggression and violence are, to find out what their possible psychobiological causes are, as we consider that the study of the psychobiological mechanisms of aggression will allow a better understanding of the evolution of this human behaviour, and also a better classification of the pathological signs of the violent behaviours. We define violence as a destructive aggression that implies physical harm to people or their properties , as those properties are instruments of life for the person assaulted or a symbol of it. We show the different psychobiological models: genetic, endocrinological, ethological and neurobiological, describing how some kinds of pathological impulsive violent behavious, can be studied as a behaviour problem with biological conexions.